Downy mildew control in pearl millet through nutrient application - D. SINGH*, G.K. GUPTA and (Indian Phytopathology, 2002)
Soil application of boron (2.5 p.p.m.) was effective in controlling primary incidence of downy mildew (Sclerospora graminicola) in pearl millet (Pennisetum glaucum). Application resulted in 76.4% lower primary incidence at 35 days after sowing compared with the control. Application of Zn (5 p.p.m.) and Fe (5 p.p.m.) was also effective. When N+P+K (10 p.p.m. each) were applied together, a reduction of 23.8% in disease incidence over the control was observed.